Functional Properties of Yellowfin Tuna (Thunnus albacares) Skin Collagen Hydrolysate Fraction Obtained By Ultrafiltration Purification. - BINH CONG NGUYEN; HONG MINH XUAN NGUYEN; KHA HOANG NAM NGUYEN; TUYEN CHAN KHA (Current Research in Nutrition & Food Science, 2021)
Hydrolyzed collagen with different fractions is broadly applied in various industries due to its functional properties. Thestudyaimedto purify and fractionate the hydrolyzed collagen from yellowfin tuna skin by ultrafiltration and evaluate the functional propertiesof its fractions. The effect of temperature, pH, and pressure on membrane flux, nitrogen recovery efficiency, and degree of separation was investigated.2 Afterward, several functional properties of hydrolyzed collagen fractions including solubility, emulsification, foaming, and antioxidant properties were evaluated. The optimum ultrafiltration conditions for hydrolyzed collagen were temperature 25°C, pH 6.5 and pressure 12psi provided optimum membrane flux (3.4 L/m2.h) and nitrogen recovery efficiency (80.81%), and the smallest degree of separation (27.45%). The products after ultrafiltration were separated into two fractions, F2 (< 3 kDa), and F1 (3-5 kDa), with the volume of 90% and 10%, respectively. Both hydrolyzed collagen fractions were more than 96% soluble at pH below 8.0, where the F2 fraction dissolved better than F1. As pH was higher than 8.0, both fractions were almost completely dissolved. In addition, the emulsifying and foaming abilities of the F1 fraction were better than the F2. However, the F2 fraction was more resistant to oxidation with higher antioxidant activity. In conclusion, this research indicates that different fractions from hydrolyzed collagen from yellowfin tuna skin have various functional properties that could be applied in food, cosmetic and pharmaceutical industries.